Analisis peran konsultan pajak terhadap kepatuhan wajib pajak klien UMKM - Klau, Denitrius; Puspita, Wulan Dri (Jurnal Ilmiah Bisnis dan Perpajakan (Bijak), 2025)
This research about the role of tax consultants in taxpayer compliance aims to determine the obstacles experienced by Micro, Small, and Medium Enterprises (MSMEs) taxpayers and the role of tax consultants in overcoming the challenges of MSME taxpayers. The descriptive qualitative method was used for this research. Primary data was used by conducting interviews with the interviewers that were chosen. It focuses on the role of consultants in handling problems faced by their clients, especially those who have MSME businesses. The results stated that MSMEs have several obstacles such as; the lack of human resources who are experts in the field of taxation, ignorance of the use of tax applications, lack of socialization and tax information obtained by taxpayers, ignorance of tax payment times, difficulty in calculating sales turnover, awareness in paying taxes, no financial bookkeeping and storing evidence of transactions. So consultants will provide solutions in the form of tax service consultation services which are; sharing information about tax regulations, optimizing the role of taxpayers, reminding tax payment dates, providing sales report creation services, providing solutions in collecting transactions, and using Tax Avoidance.